The Role of Social Cognitive Perspective on Investment Intentions in Sharia Stocks in Indonesia - Dewi, Cynthia Sari; Daffa Juliansyah, Muhammad; Anakoda, Valdy Ivanda; Parikesit, Bangun (The Eastasouth Management and Business, 2024)
The majority of Indonesia's population recorded in 2024 will be Muslims, reaching 85% with a figure of 263 million out of a total population of more than 278 million people. However, the level of public investment in shares is still low, especially in sharia shares. The aim of this research is to examine the impact of attitudes, social influence, and self-confidence on Indonesian investors' intentions to invest in sharia shares. This will be achieved by exploring further with Social Cognitive Theory. This research uses a quantitative methodology which is used to collect data from a minimum sample size of 85 respondents. This research was conducted by giving questionnaires to investors who have knowledge about sharia shares in Indonesia. The expected result of this research is to increase understanding of the determining factors that influence investment intentions in sharia shares. Therefore, this research is expected to provide a significant contribution to policy makers in their efforts to increase the number of investors in Islamic stocks.